Blueprint 2050 : Sustaining the Marine Environment in Mainland Tanzania and Zanzibar - World Bank (Washington, DC : World Bank, 2012)
Protection of sound management of coastal and marine areas is acknowledged as important mechanisms for alleviating poverty in the developing tropics. Tanzania has had considerable practical experience with a diversity of models that rely on private sector partnerships, community co-management regimes, and government-led initiatives for marine protection. This report outlines a vision of what a protected area system could look like in 50 years. It draws on state-of-the-art ecosystems, socioeconomic, financial, and institutional background studies, to paint a picture that emphasizes community-based adaptive co-management, within a flexible system of eight protected area networks, on of which is the Exclusive Economic Zone.